Investigation of hydrogen adsorption and absorption in palladium thin films. II. Cyclic voltammetry - GABRIELLI, C; GRAND, P. P; LASIA, A; PERROT, H (Journal of the Electrochemical Society, 2004)
Hydrogen absorption into palladium thin films (10 monolayers and 100 mm) was studied using cyclic voltammetry. The behavior of thin layers prepared by electrodeposition is different from that of the bulk Pd. On very thin films hydrogen adsorption, absorption, and evolution processes are separated. Adsorption kinetics depends strongly on applied potential and layer thickness. A new method is proposed for the determination of the quantity of adsorbed hydrogen in the presence of the absorption process.